1979
DOI: 10.1159/000207658
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Involvement in Thalassemia Major

Abstract: The auditory function of 75 children affected by homozygous β°-thalassemia, managed with a low transfusion scheme and treated irregularly with low doses of desferrioxamine, and of 75 controls were examined. In 12 patients a mild bilateral conductive hearing impairment due to bony hypertrophy and/or adenoid hypertrophy was found. In 43 cases a moderate monolateral or bilateral sensory-neural hearing loss at high frequencies with recruitment phenomenon was observed. Ferritin levels were determined in a randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 11 publications
(14 reference statements)
2
23
0
Order By: Relevance
“…From 57.33% patients with sensorineural hearing impairment, bilateral hearing impairment was found in 41.33% patients and unilateral hearing impairment in 16% patients. 4 Hearing impairment was mostly found in age group between 7 to 12 years, nine patients (13.9%), with means 9.9 (SD 4.5) years. Argioulu et al found hearing impairment in 15.5% patients with mean 11.5 (SD 3) years, 6 Kontzoglou et al demonstrated mean 9.66 (SD 3.1) years, 18 and Gallant demonstrated mean 12 years.…”
Section: The Features Of Hearing Impairment In Thalassemia Majormentioning
confidence: 92%
See 4 more Smart Citations
“…From 57.33% patients with sensorineural hearing impairment, bilateral hearing impairment was found in 41.33% patients and unilateral hearing impairment in 16% patients. 4 Hearing impairment was mostly found in age group between 7 to 12 years, nine patients (13.9%), with means 9.9 (SD 4.5) years. Argioulu et al found hearing impairment in 15.5% patients with mean 11.5 (SD 3) years, 6 Kontzoglou et al demonstrated mean 9.66 (SD 3.1) years, 18 and Gallant demonstrated mean 12 years.…”
Section: The Features Of Hearing Impairment In Thalassemia Majormentioning
confidence: 92%
“…Gallant et al demonstrated mild hearing impairment in 7.86% patients and moderate hearing impairment in 16.85% patients, 8 whereas other investigator demonstrated moderate hearing impairment in all of their patients. 4 Regarding to sex proportion, males were close to females in proportion (DeVirgilis 4 and Bentur).…”
Section: Grade Of Hearing Impairmentmentioning
confidence: 95%
See 3 more Smart Citations